Efeito hepatoprotetor do ácido ascórbico e potencial benéfico da via oral na quimioterapia antimonial em modelo murino de leishmaniose visceral - Kelly Cristina Kato (2013)
Pentavalent antimonials are the first-line drugs in several countries worldwide for treatment of leishmaniasis, as it is the case of meglumine antimoniate in Brazil. Despite its high efficacy, antimonial chemotherapy shows important limitations, such as the need for repeated parenteral doses and several side effects that limit patient compliance. The scarce knowledge about the chemical composition of these drugs and the mechanisms responsible for their toxicity has also hindered progress towards the improvement of antimonial chemotherapy. In the search for strategies to reduce pentavalent antimony toxicity during leishmaniasis treatment, we investigated the chemical composition of meglumine antimoniate, the role of residual trivalent antimony (Sb(III)) in the drug hepatotoxicity in a murine model of visceral leishmaniasis (VL), the effect of co-treatment with the antioxidant ascorbic acid (AA) and the potential benefit of the oral route of administration. The physicochemical characterization of the synthetic (AM1 and AM) and commercial (Gluc) forms of meglumine antimoniate showed the predominance of a zwitterionic 2:2 Sbmeglumine complex in AM1 and AM and of a positively-charged 2:3 Sb-meglumine complex in Gluc. The Sb(III) content determined by voltammetry showed, in Gluc, 24% of total Sb and, in AM1, 1.5 times lower level. The Sb(III) contents found by photometry were much smaller and in the following order: AM > Gluc > AM1. AM also showed significant levels of the potentially toxic trace elements, Pb and As. The compounds AM, AM1 and Gluc showed equivalent antileishmanial efficacies following parenteral treatment in BALB/c mice infected with L. infantum. However, only AM and Gluc promoted hepatotoxicity, as evidenced by histopathological analysis and apoptotic index of hepatocytes. The increase of peroxidase activity in the liver of animals treated with AM and Gluc suggested an induction of oxidative stress. The lower hepatotoxicity of AM1 correlated with its lower level of Sb(III), indicating that the residual Sb(III) may contribute to Gluc hepatotoxicity. The cotreatment of infected mice with AA significantly reduced the hepatotoxicity of Gluc, without compromising its antileishmanial efficacy. AM and AM1 given orally to mice showed a higher rate of intestinal absorption and an increased hepatic concentration of Sb, when compared to Gluc. The synthetic compounds showed higher effectiveness by the oral route than the commercial drug, when evaluating the supression of spleen parasite in mice infected with L. infantum. In conclusion, this thesis identified three promising strategies to reduce the side effects of antimonial chemotherapy: the use of pentavalent antimony with low content of Sb(III), the cotreatment with AA and the use of the oral route for treatment of the LV.